Firms' Debt Covenant and Accruals Based Earnings Management: Empirical Evidence from Thai Listed Companies - สุริยะสาร, ฐิฏิกานต์ (วารสารการบัญชีและการจัดการ, 2023)
This research aims to investigate firms' debt covenant and accruals-based earnings management through the earnings management discretion in order to maintain the terms of the loan agreement of firms listed in the Stock Exchange of Thailand. The data samples are 1,772 firms collected from 2014 to 2018. Multiple regression is employed to test the hypotheses. The results show that an increasing in debt covenant was a positive relationship to accruals-based earnings management of Thai listed firms. In addition, MAI listed firms have accruals-based earnings management more than Thai-listed firms. Management level has incentives regarding to debt covenants profits, management, posted on an accrual basis of listed firms.